The genus Arachnomimus Saussure, 1897 (Orthoptera: Phalangopsidae) in India, with description of a new subgenus and species from a cave in Chhattisgarh, India - Jaiswara, Ranjana; Monaal, Monaal; Desutter-Grandcolas, Laure (Zootaxa, 2021)
The genus Arachnomimus Saussure, 1897 is one of the 13 genera of Phalangopsidae present in India. A total of 11 species belongs to this genus, of which, 9 are grouped in the subgenus Arachnomimus Saussure, 1897 with their distribution on the Indian subcontinent. One species occurs in Brazil and another in Euarachnomimus Gorochov, 1996 known from Southeast Asia. India hosts two species, Arachnomimus (Arachnomimus) lepidus Chopard, 1969 and Arachnomimus (Arachnomimus) maindroni (Chopard, 1969). In the present paper, we describe a new subgenus, Indimimus Desutter-Grandcolas & Jaiswara and a new species Indimimus jayanti Jaiswara under genus Arachnomimus. Identification keys for all the three subgenera and three species from India are proposed.